An international investigation into AB plasma administration in hospitals: how many AB plasma units were infused? The HABSWIN study. Issue 1 (14th October 2017) - Zeller, Michelle P.; Barty, Rebecca; Dunbar, Nancy M.; Elahie, Allahna; Flanagan, Peter; Garritsen, Henk; Kutner, José Mauro; Pagano, Monica B.; Pogłód, Ryszard; Rogers, Thomas S.; Staves, Julie; van Wordragen‐Vlaswinkel, Maria; et al.
Abstract : BACKGROUND: Typical practice is to transfuse group‐specific plasma units; however, there are situations where group AB plasma (universal donor) is issued to group A, B, or O recipients. If demand for group AB plasma exceeds collections, there is potential for shortage. This project explored the patterns of group AB plasma utilization at hospitals around the world. STUDY DESIGN AND METHODS: The study had two phases: a survey that inquired about hospital group AB plasma inventory, policies, and transfusion practices and a retrospective review of 2014 calendar year data where participants submitted information on plasma disposition including ABO group of unit and recipient, transfusion location, and select indications. Recruitment occurred through snowball sampling. Descriptive analyses were performed. RESULTS: Survey data were received from 25 centers across 10 countries; of those, 15 participants contributed to the data collection component. These 15 centers transfused a total of 43, 369 AB plasma units during the study period. Only 1496 of 5541 (27%) group AB plasma units were transfused to group AB recipients. Transfusion policies, practices, and patterns were variable across sites. CONCLUSION: Group AB plasma units are frequently transfused to non‐AB recipients. Whether transfusing 73% of group AB plasma units to non‐AB recipients is the ideal inventory management strategy remains to be determined.